Association Between Partial Pressure of Arterial Carbon Dioxide and Survival to Hospital Discharge Among Patients Diagnosed With Sepsis in the Emergency Department. Issue 3 (March 2018) - Roberts, Brian W.; Mohr, Nicholas M.; Ablordeppey, Enyo; Drewry, Anne M.; Ferguson, Ian T.; Trzeciak, Stephen; Kollef, Marin H.; Fuller, Brian M.
Abstract : Objective: The objective of this study was to test the association between the partial pressure of arterial carbon dioxide and survival to hospital discharge among mechanically ventilated patients diagnosed with sepsis in the emergency department. Design: Retrospective cohort study of a single center trial registry. Setting: Academic medical center. Patients: Mechanically ventilated emergency department patients. Inclusion criteria: age 18 years and older, diagnosed with sepsis in the emergency department, and mechanical ventilation initiated in the emergency department. Interventions: Arterial blood gases obtained after initiation of mechanical ventilation were analyzed. The primary outcome was survival to hospital discharge. We tested the association between partial pressure of arterial carbon dioxide and survival using multivariable logistic regression adjusting for potential confounders. Sensitivity analyses, including propensity score matching were also performed. Measurements and Main Results: Six hundred subjects were included, and 429 (72%) survived to hospital discharge. The median (interquartile range) partial pressure of arterial carbon dioxide was 42 (34–53) mm Hg for the entire cohort and 44 (35–57) and 39 (31–45) mm Hg among survivors and nonsurvivors, respectively ( p < 0.0001 Wilcox rank-sum test). On multivariable analysis, a 1 mm Hg rise in partial pressure of arterial carbon dioxide was associated with a 3% increase in odds of survival (adjusted odds ratio, 1.03; 95% CI, 1.01–1.04) after adjusting for tidal volume and other potential confounders. These results remained significant on all sensitivity analyses. Conclusion: In this sample of mechanically ventilated sepsis patients, we found an association between increasing levels of partial pressure of arterial carbon dioxide and survival to hospital discharge. These findings justify future studies to determine the optimal target partial pressure of arterial carbon dioxide range for mechanically ventilated sepsis patients. Abstract : Supplemental Digital Content is available in the text.